I rise ebook - Arnold, Marie (2022)
"A love letter to Harlem and hope. I Rise is smart and funny and full of heart.*" Fourteen-year-old Ayo who has to decide whether to take on her mother's activist role when her mom is shot by police. As she tries to find answers, Ayo looks to the wisdom of her ancestors and her Harlem community for guidance. Ayo's mother founded the biggest civil rights movement to hit New York City in decades. It's called 'See Us' and it tackles police brutality and racial profiling in Harlem. Ayo has spent her entire life being an activist and now, she wants out. She wants to get her first real kiss, have a boyfriend, and just be a normal teen. When her mom is put into a coma after a riot breaks out between protesters and police, protestors want Ayo to become the face of See Us and fight for justice for her mother who can no longer fight for herself. While she deals with her grief and anger, Ayo must also discover if she has the strength to take over where her mother left off. This impactful and unforgettable novel takes on the important issues of inequality, systemic racism, police violence, and social justice. *Kwame Alexander, New York Times bestselling author